Physical strain during activities of daily living of patients with coronary artery disease. (1st July 2013) - Nieuwenburg‐van Tilborg, E. M.; Horstman, A. M.; Zwarts, B.; de Groot, S.
Summary The purpose of this study was to determine the physical strain of activities of daily living (ADL) in patients with coronary artery disease (CAD) compared with healthy controls. Seventeen patients with CAD and 15 controls performed a graded exercise bicycle test and 5 ADL tasks: walking with/without load, vacuum cleaning, undressing, and walking stairs. Peak heart rate (HRpeak) and peak oxygen uptake (VO2peak) were determined during the bicycle test. Heart rate (HR) and oxygen uptake (VO2) were continuously measured during all ADL tasks. Physical strain during ADL tasks was calculated using HR and VO2 response, expressed relative to individual HR and VO2 reserves (%HRR, %VO2R, respectively). Perceived strain was measured using the Rating of Perceived Exertion (RPE) scale. HRpeak and VO2peak were lower (P<0·001) in patients. Patients performed the ADL tasks slower and with lower absolute VO2, except for undressing. HR was only higher in patients during stair climbing. No differences in RPE scores were found between both groups, except for undressing. However, physical strain was significantly higher in patients (mean %VO2R ranged from 43% to 51%; mean %HRR ranged from 38% to 47%) compared with controls (mean %VO2R: 14% to 30%; mean %HRR: 14% to 29%) for all ADL tasks. In general, ADL tasks were performed slower and with higher physical strain in patients with CAD compared with controls.